Transcendental Ethics between Islam and the West: An Analysis of the Fatwa of the National Sharia Council of the Indonesian Ulema Council on Usury in Murabahah - Iksan, Iksan; Wardiono, Kelik; Yuspin, Wardah; Absori, Absori; Ridwan, Ridwan; Nuswanto, Albertus Heru (Journal of Ecohumanism, 2024)
Objective: This study aims to analyze the aspects of transcendent ethics between Islam and the West as material for analyzing the aspect of usury in the DSN-MUI fatwa on murabahah. Theoretical Framework: This paper used the philosophy of axiology or philosophy of values as a theoretical framework. It also uses the prophetic paradigm. Method: This study uses a normative-philosophical legal research method. The type of data is secondary with a literature review to obtain data. While the data analysis uses descriptive analysis, interpretation, and hermeneutics. Results and Discussion: The results of the study show that the fatwa on murabahah, especially those related to the regulation of usury as stated in the DSN-MUI fatwa No. 04/DSN-MUI/IV/2000, shows that Islamic ethics is still mixed with western ethics, especially Protestant ethics in Max Weber's understanding. This happens because there is a clause in the general provisions that allows customers to buy their own goods using the wakalah contract. Research Implications: The implication is that researchers must be more and more productive in discussing and writing about murabahah. This research is limited to the DSN-MUI fatwa and ethics to understand usury in murabahah so it needs to be expanded again with other aspects, such as contracts, guarantees, discounts and others. Originality/Value: Research on murabahah and the DSN-MUI fatwa has been widely conducted by researchers both in Indonesia and the world. However, research that discusses aspects of Islamic and Western ethics as a barometer for assessing fatwas is still very rarely conducted by researchers. So, this research is very important to add references and different perspectives to assess fatwas.